Tourism and Cultural Landscapes in Southern China’s Highlands - Zhe Wang; Nelson Graburn (Via@)
Cultural landscapes are combined work of man and nature. In 1992, the World Heritage Convention adopted the cultural landscape in the World Heritage List. In Asia, the ongoing urbanization and rural-urban migration have threatened the continuing cultural landscapes as people leave their homes. Tourism has brought new challenges and opportunities to these areas, while its impacts on the cultural landscape are inadequately researched. This paper aims to fill the gap through case studies of two subtropical rice terraced field cultural landscapes in China’s highlands. A stakeholder approach is applied in understanding the attitudes and practices of different agents towards terraced fields and traditional villages. Mixed method research, including researching secondary materials, in-depth interviews, participant observation, and questionnaire surveys were conducted on local households and other stakeholders. The continuing urbanization process threatens the cultivation traditions by displacing agricultural livelihoods, rural-urban migration, and enabling young generations to abandon work on the farmlands. Tourism may slow down the loss of terraced fields by providing alternative opportunities and attracting people to return from the cities, while the commodification in tourism businesses also led to dramatic changes to the village landscapes. The continuing cultural landscapes are created collaboratively by people and nature, and by the collaborative practice of people. Effective management policies on cultural landscapes must put their creators and their livelihoods at the center rather than the physical manifestations. Tourism and conservation policies should evaluate the interests of all stakeholders and their behavioral consequences on cultural landscapes.